Enterprise Knowledge Infrastructures - Maier, Ronald; Hädrich, Thomas; Peinl, René (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Success of an organization is increasingly dependent on its capability to create an environment to improve the productivity of knowledge work. This book focuses on the concepts, models and technologies that are used to design and implement such an environment. It develops the vision of a modular, yet highly integrated enterprise knowledge infrastructure and presents an ideal architecture replete with current technologies and systems. The most important streams of technological development that are covered in the book are computer-supported cooperative work, document and content management, e-learning, enterprise portals, information life cycle management, knowledge management, mobile computing, and the Semantic Web. It includes learning goals, exercises and case examples that help the reader to easily understand and practice the concepts. The book is targeted at advanced bachelor and master students. Practitioners profit from insights into the importance of technologies and systems and their application.